Estimating genetic parameters of immunocompetent traits in Rhode Island Red chicken - DAS, ANANTA KUMAR; KUMAR, SANJEEV; MISHRA, ANIL KUMAR; RAHIM, ABDUL; KOKATE, LAXMIKANT SAMBHAJI (The Indian Journal of Animal Sciences, 2016)
The study aimed to estimate genetic parameters of immunocompetent traits in Rhode Island Red (RIR) chicken. Five to six weeks aged pedigreed RIR chicks of a selected (79 chicks) and a control (74 chicks) line maintained at the Central Avian Research Institute were immunized against 1% (v/v) SRBC suspension. Sera collected on 5th day post immunization were analyzed through haemagglutination (HA) test to assess humoral immune response. Serum lysozyme and immunoglobulin-G (IgG) concentrations were assessed through agarose lysoplate and single radial immunodiffusion assay. The data were analyzed by least squares analysis of variance. The least squares mean estimates of serum lysozyme and IgG were significantly influenced by sires in the selected line, but any estimate was not affected by sex in any line. The selected line had more serum lysozyme than the control line, which contained more HA titre and serum IgG. The traits were heritable at a range of 0.105 to 0.398, and correlated with a low to high range (0.134 to 0.552) of genetic correlations and least to low range (0.007 to 0.170) of phenotypic correlations. The information generated could be important while selecting birds for improvement in general immune responsiveness.